Combined exenatide and dapagliflozin has no additive effects on reduction of hepatocellular lipids despite better glycaemic control in patients with type 2 diabetes mellitus treated with metformin: EXENDA, a 24‐week, prospective, randomized, placebo‐controlled pilot trial. Issue 5 (10th February 2021) - Harreiter, Jürgen; Just, Ivica; Leutner, Michael; Bastian, Magdalena; Brath, Helmut; Schelkshorn, Christian; Klepochova, Radka; Krššák, Martin; Kautzky‐Willer, Alexandra
Abstract: Aims: To investigate the potential synergistic effects of combined exenatide (EXE) and dapagliflozin (DAPA) versus (PLAC) placebo and DAPA on hepatocellular lipid (HCL) reduction after 24 weeks of treatment. Materials and methods: Thirty patients with type 2 diabetes were randomized to weekly EXE and daily DAPA (n = 16) or weekly PLAC and daily DAPA (n = 14). Inclusion criteria were glycated haemoglobin (HbA1c) 48 to 97 mmol/mol (6.5‐11%), age 18 to 75 years, body mass index (BMI) ≥25 kg/m 2 and metformin ≥1000 mg. The primary endpoint, HCL levels, were measured at baseline and after 24 weeks of treatment using magnetic resonance spectroscopy. Between‐group effects were analysed using general linear models, adjusted for baseline outcome variables, age, sex and BMI. Within‐group differences were assessed using a paired t ‐test. Results: After 24 weeks, HCLs were reduced in both treatment groups (absolute change from baseline: EXE + DAPA −4.4%, 95% confidence interval [CI] −8.2, −0.7, P < 0.05; PLAC + DAPA −3.9%, 95% CI −6.0, −1.7, P < 0.01; relative change: EXE + DAPA −35.6%, PLAC + DAPA −32.3%) with no difference between groups. Similar findings were observed for subcutaneous adipose tissue (SAT) and visceral adipose tissue (VAT). HbA1c (EXE + DAPA −17.8 mmol/mol, [95% CI −24.8, −10.8], P <0.001; PLAC + DAPA −6.9 mmol/mol, [95% CI −10.5, −3.3], P = 0.001) and fasting glucose significantly decreased in both groups, although EXE + DAPA achieved better glycaemic control than PLAC + DAPA (adjusted difference: HbA1c −6.0 mmol/mol [95% CI −9.7, −2.2], P < 0.01). Body weight was reduced in both treatment groups (EXE + DAPA −7.3 kg, 95% CI −9.9, −4.8, P <0.001; PLAC + DAPA −4.6 kg, 95% CI −7.4, −1.8, P <0.01) with comparable results between groups. Changes in HCLs and weight, hip and waist circumference, VAT and SAT were positively associated. Conclusion: After 24 weeks, HCLs were significantly but comparably reduced in the EXE + DAPA and PLAC + DAPA groups, despite significantly better glycaemic control in the combined group EXE + DAPA. Changes in HCLs were associated with weight loss and reduction of visceral adiposity, but not with glucose control. Further studies are necessary to evaluate possible additional long‐term effects of a combined treatment.